PENGGUNAAN SOFTWARE ELECTRONIC WORK BENCH (EWB) UNTUK PELATIHAN PERANCANGAN PEMBUATAN RANGKAIAN ELEKTRONIKA DI KALIREJO KABUPATEN PASURUAN (JPMPPI (Jurnal Pengabdian Masyarakat), 2022)
The development of technology today is very much needed, especially knowledge of computers. Expertise in the computer field, namely expertise in the field of hardware (hardware) and software (software). The usability of software is very important to help human work become faster and more efficient. One of the software that can help ease in making simulations in the field of computer electronics is the Electronic Work Bench (EWB). Electronic work bench is one of the electronic computer software that can be used to simulate an electronic circuit both analog and digital. The purpose of this community service activity is that participants can operate electronic work bench software as tools to solve problems in the environment where participants are located. This activity was held on 28-29 July 2022 and was attended by 20 residents of Bangil. The implementation method is carried out in 3 stages, namely planning, implementation, and evaluation. The results obtained from this activity are that participants can increase their basic knowledge and improve their operating skills on electronic work bench software.